COVID-19 Mortality in Rich and Poor Countries : A Tale of Two Pandemics? - Schellekens, Philip; Sourrouille, Diego (World Bank, Washington, DC, 2020)
COVID-19 can be described as a heat-seeking missile speeding toward the most vulnerable in society. That metaphor applies not just to the vulnerable in the rich world; the vulnerable in the rest of the world are not more immune. Yet, despite the extensive spread of the virus, the mortality toll remains highly concentrated in high-income countries. Developing countries represent 85 percent of the global population, but only 21 percent of the pandemic's death toll. This unusual inequality creates the impression that the world is subjected to two different pandemics in terms of their impact. This paper documents the observed inequality with a new indicator that expresses severity relative to pre-pandemic patterns. It argues that the excessive skew towards rich countries is inconsistent with demography. Simulations based on reasonable ranges for infectivity and fatality suggest that the developing country share in global fatalities could rise by a factor of three (from 21 to 69 percent). Environmental and host-specific factors will influence these results but are unlikely to overturn them. While data quality has a role in explaining ‘excess inequality’, the more compelling explanation is that the pandemic has yet to run its course through the age distributions of the world.